The etiopathogenesis and the new classification system of rosacea [Rozase etyopatogenezi ve yeni siniflamasi] - (:unkn) unknown (My University, 2007)
Rosacea is a chronic, recurrent and an insflammatory disorder of the skin. It is most often characterized by transient or persistent central facial erythema, telangiectases, and often papules and pustules. Although several hypotheses have been documented on the etiopathogenesis of rosacea, the exact cause still remains unknown. Psychogenic, racial, infectious, immunological and vascular theories have been proposed. Recently, a new classification system of rosacea is reported by an expert committe assembled by The National American Rosacea Society. According to this committee, 4 subtypes of rosacea including erythematotelangiectatic, papulopustular, phymatous, and ocular are defined. Current pathogenic theories on rosacea and this new classification system is reviewed in this manuscript.
Keywords: Pathogenesis; Rosacea; Subtypes